Modelling and Simulation of Damping Controller in DFIG AND PMSG Integrated with a Convectional Grid: a Review - Sabo Aliyu; Dauda Dahiru; Noor Izri Abdulwahab (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
Wind energy conversion systems stand out as one of the most abundant sources of energy provided by nature. These systems are highly sustainable and environmentally friendly, as they do not generate pollution. Damping controllers are specifically designed to enhance the robustness and adaptability of hybrid systems utilizing permanent magnet and double-fed induction synchronous generators. These generators are carefully integrated with conventional energy sources, necessitating a vigilant focus on grid stability, particularly rotor angle stability. This stability is crucial for preventing mechanical oscillations and potential disruptions in the grid caused by instability. Furthermore, power system stabilizers with excitation systems are carefully designed and optimized to maximize damping performance while minimizing energy losses. In this context, damping controllers play a vital role.